Robust thermal control for CMOS-based lab-on-chip systems. (22nd May 2015) - Martinez-Quijada, Jose; Ma, Tianchi; Hall, Gordon H; Reynolds, Matt; Sloan, David; Caverhill-Godkewitsch, Saul; Glerum, D Moira; Sameoto, Dan; Elliott, Duncan G; Backhouse, Christopher J
Abstract: The need for precise temperature control at small scales has provided a formidable challenge to the lab-on-chip community. It requires, at once, good thermal conductivity for high speed operation, good thermal isolation for low power consumption and the ability to have small (mm-scale) thermally independent regions on the same substrate. Most importantly, and, in addition to these conflicting requirements, there is a need to accurately measure the temperature of the active region without the need for device-to-device calibrations. We have developed and tested a design that enables thermal control of lab-on-chip devices atop silicon substrates in a way that could be integrated with the standard methods of mass-manufacture used in the electronics industry (i.e. CMOS). This is a significant step towards a single-chip lab-on-chip solution, one in which the microfluidics, high voltage electronics, optoelectronics, instrumentation electronics, and the world-chip interface are all integrated on a single substrate with multiple, independent, thermally-controlled regions based on active heating and passive cooling.